Electronic state transition in cooperatively interacting point-defects in semiconductor crystals - Mohamed, Mohd Ambri; Majlis, Yeop Burhanuddin; Ani, Mohd Hanafi (IEEE, 2014)
Electron state transition of deep level point defects in a semiconductor crystal was studied. Low-temperature grown GaAs produced excess antisite As (AsGa) which produces localized spin when doped with Be. A nearly abrupt decrease of 1.7% of the resistance is detected at a temperature around 4 K which is consistent with abrupt decrease of magnetization. These observations are explained as a result of cooperative transition of electron states of AsGa defects. First-principal calculations of the electron state of an AsGa atom with a shallow acceptor Be show that at the transition an AsGa+ ion is displaced to the interstitial site and becomes a neutral atom and finally results in formation of a hole producing enhancement in conductivity.